GaAs semiconductor laser epitaxial wafer and preparation method thereof
Patent Information
- Application Number
- CN202510681614.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-26
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-05-26
AI Technical Summary
然而,这种方法存在显著局限性:由于脊型结构的宽度通常仅为几微米至几十微米,石墨层与半导体材料的有效接触面积较小,导致界面热阻难以降低
1.本发明的GaAs半导体激光器外延片,通过在该结构中嵌入一层石墨纳米片作为散热层,降低腔面因非辐射复合产生的热量,避免因过高的温度形成热击穿使腔面或体材料产生局部熔化,从而避免COD现象发生。
Smart Images

Figure CN120638033B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of optoelectronics technology, and more particularly to a GaAs semiconductor laser epitaxial wafer and its fabrication method, which improves the heat dissipation capability of the laser by introducing graphite nanosheets into the GaAs semiconductor laser epitaxial structure. Background Technology
[0002] High-power semiconductor lasers, due to their high conversion efficiency and reliability, have important applications in solid-state pumping sources, industrial processing, and laser medicine. However, their development faces severe heat dissipation challenges. Even with conversion efficiencies of 50%–70%, these lasers still dissipate a significant amount of energy as heat, resulting in active region heat flux densities on the order of kW / cm². Furthermore, nonradiative recombination caused by material defects or interface states further exacerbates heat accumulation. For example, the thermal conductivity of GaAs-based lasers decreases significantly with increasing temperature, from 55 W / (m·K) at 300 K to 32 W / (m·K) at 500 K. This nonlinear degradation severely restricts heat dissipation capabilities. In traditional large cavity waveguide structures, increasing the waveguide layer thickness can expand the optical field distribution of the semiconductor laser epitaxial structure, reduce the optical confinement factor in the active region, and suppress the cavity surface optical catastrophic damage (COD) phenomenon. However, large cavity and thick waveguides lead to an increase in the laser threshold current and series connection, which is not conducive to the development of devices. Although tensile strain quantum well structures can reduce cavity surface light absorption by releasing biaxial stress and increasing the band gap, their universality is insufficient due to limitations in the material system.
[0003] The application of graphite nanosheets in laser heat dissipation is currently mainly limited to back-end processes, namely, their introduction during ridge etching after epitaxial growth. However, this method has significant limitations: since the width of the ridge structure is typically only a few micrometers to tens of micrometers, the effective contact area between the graphite layer and the semiconductor material is small, making it difficult to reduce the interfacial thermal resistance.
[0004] Therefore, there is an urgent need to apply graphite nanosheet heat dissipation technology to GaAs high-power lasers. Through the synergistic optimization of materials, structure and process, we can break through the limitations of traditional heat dissipation methods and promote the further improvement of the performance of high-power semiconductor lasers. Summary of the Invention
[0005] This invention aims to overcome the shortcomings of existing technologies by providing a semiconductor laser epitaxial wafer and its fabrication method. The invention atomizes a graphite nanosheet dispersion into an aerosol, which is then fed into a reaction chamber along with AsH3 via H2. This aerosol, combined with an N-confinement layer, shortens the heat dissipation path, rapidly removes heat from the active region, improves the laser's heat dissipation capacity and operational reliability, effectively suppresses COD (Chemical Oxygen Depletion) phenomena, and extends device lifespan, providing technical support for the development of higher-power and more stable semiconductor lasers.
[0006] The technical solution adopted by this invention to solve its technical problem is: An epitaxial wafer for a GaAs semiconductor laser is epitaxially grown on a GaAs substrate using MOCVD technology. From bottom to top, it comprises a GaAs buffer layer, an AlN dielectric layer, a graphite nanosheet N-confinement layer, an N-waveguide layer, a lower barrier layer, a quantum well layer, an upper barrier layer, a P-waveguide layer, a P-confinement layer, and a GaAs ohmic contact layer. The GaAs buffer layer alleviates lattice mismatch and thermal expansion coefficient differences between the substrate and the epitaxial layer. The AlN dielectric layer alleviates interfacial stress between the buffer layer and the N-confinement layer. The graphite nanosheet N-confinement layer restricts electron diffusion to the P-side through a high bandgap and confines the light field near the active region using its low refractive index. The N-waveguide layer and P-waveguide layer have refractive indices between the confinement layer and the active region, constraining the laser mode in the vertical growth direction and assisting electron injection into the active region. The lower barrier layer, quantum well layer, and upper barrier layer together constitute a quantum well structure, confining charge carriers within the quantum well. The GaAs ohmic contact layer forms a low-resistance ohmic contact with a metal electrode.
[0007] The graphite nanosheet N-confinement layer is an Alx1Ga1-x1As graphite nanosheet N-confinement layer, the waveguide layer is an Alx2Ga1-x2As N-waveguide layer, the lower barrier layer is an Alx3Ga1-x3As lower barrier layer, the quantum well layer is an Inx4Ga1-x4As quantum well layer, the upper barrier layer is an Alx5Ga1-x5As upper barrier layer, the P-waveguide layer is an Alx6Ga1-x6As P-waveguide layer, and the P-confinement layer is an Alx7Ga1-x7As P-confinement layer.
[0008] The method for fabricating GaAs semiconductor laser epitaxial wafers includes the following steps: 1) Place the GaAs substrate in the reaction chamber of the MOCVD equipment, and introduce AsH3 in an H2 environment to perform high-temperature heat treatment on the GaAs substrate to remove water and oxygen on the substrate surface, forming an atomically clean GaAs surface, ensuring atomic-level bonding between the epitaxial layer and the substrate; after introducing AsH3, the arsenic atmosphere generated by the decomposition of AsH3 maintains a high arsenic partial pressure in the reaction environment, inhibiting the decomposition of GaAs, protecting the structural and compositional stability of the substrate, and avoiding crystal structure damage and compositional changes caused by arsenic volatilization. The temperature of the high-temperature heat treatment is 600-750℃, and the heat treatment time is 10-20 minutes. 2) The reaction chamber temperature is maintained at 710-730℃, and TMGa and AsH3 are introduced to grow a GaAs buffer layer with a thickness of 100-200nm on the GaAs substrate. The doping source is Si2H6. 3) When the reaction chamber temperature drops to 650-700℃, NH3 is first introduced for pre-passivation, and then TMAl is introduced to grow an AlN nucleation layer with a thickness of 2-5nm on the GaAs buffer layer; when the reaction chamber temperature rises to 800-900℃, an AlN epitaxial layer with a thickness of 5-10nm is grown on the AlN nucleation layer. 4) When the temperature of the reaction chamber drops to 550-650℃, TMAl, TMGa, AsH3 and graphite nanosheet aerosol are introduced to grow an Alx1Ga1-x1As graphite nanosheet N-confined layer with a thickness of 1-3μm on the AlN epitaxial layer, with Si2H6 as the doping source. 5) After step 4) is completed, the temperature of the reaction chamber is raised to 680-700℃, and then TMAl, TMGa and AsH3 are introduced to grow an Alx2Ga1-x2AsN waveguide layer with a thickness of 0.5-1.5μm and Si2H6 as the doping source. 6) After step 5) is completed, the temperature of the reaction chamber is reduced to 550-570℃, and then TMGa and AsH3 are introduced to grow the Alx3Ga1-x3As lower barrier layer with a thickness of 20-30nm. 7) After step 6) is completed, maintain the reaction chamber temperature at 550-570℃, and then introduce TMI, TMI, and AsH3 to grow an Inx4Ga1-x4As quantum well layer with a thickness of 5-10 nm. 8) After step 7 is completed, the temperature of the reaction chamber is reduced to 550-570℃, and then TMGa and AsH3 are introduced to grow the Alx5Ga1-x5As upper barrier layer with a thickness of 20-30nm. 9) After step 8 is completed, the temperature of the reaction chamber is raised to 650-690℃, and then TMAl, TMGa and AsH3 are introduced to grow an Alx6Ga1-x6As P waveguide layer with a thickness of 0.2-0.7μm and CBr4 as the doping source. 10) After step 9 is completed, maintain the reaction chamber temperature at 650-690℃, and then introduce TMAl, TMGa and AsH3 to grow an Alx7Ga1-x7As P confinement layer with a thickness of 0.5-1μm and CBr4 as the doping source. 11) When the temperature of the reaction chamber drops to 540-560℃, TMGa and AsH3 are introduced to grow a GaAs ohmic contact layer with a thickness of 200-400nm on the Alx7Ga1-x7As P confinement layer, with CBr4 as the doping source.
[0009] The temperature of the high-temperature heat treatment in step 1) is 730-750℃, and the baking time is 10-20 minutes.
[0010] The reaction chamber temperature in step 2) is 720℃, the growth thickness is 150nm, and the doping concentration is 1E18~3E18 atoms / cm³. In step 4), when the reaction chamber temperature is 600℃, the growth thickness is 2μm, 0.3≤x1≤0.6, and the doping concentration is 5E17~2E18 atoms / cm³.
[0011] In step 5), the reaction chamber temperature is 690℃, the growth thickness is 1.0μm, 0.2≤x2≤0.3, and the doping concentration is 5E17~2E18 atoms / cm³.
[0012] In step 6), the reaction chamber temperature is 560℃, the growth thickness is 25nm, and 0.2≤x3≤0.3; In step 7), the reaction chamber temperature is 560℃, and the growth thickness is 7nm; 0.1≤x4≤0.3; In step 8), the reaction chamber temperature is 560℃, the growth thickness is 25nm, and 0.2≤x3≤0.3.
[0013] In step 9), the reaction chamber temperature is 670℃, the growth thickness is 0.5μm, 0.1≤x6≤0.3, and the doping concentration is 2E17~9E17 atoms / cm³. In step 10), the reaction chamber temperature is 670℃, the growth thickness is 0.8μm, 0.6≤x7≤0.9, and the doping concentration is 9E17~2E18 atoms / cm³.
[0014] In step 11), the reaction chamber temperature is 550℃, the growth thickness is 300nm, and the doping concentration is 1E19~4E19 atoms / cm³.
[0015] The beneficial effects of this invention are: 1. The GaAs semiconductor laser epitaxial wafer of the present invention reduces the heat generated by nonradiative recombination at the cavity surface by embedding a layer of graphite nanosheets as a heat dissipation layer in the structure, thereby avoiding local melting of the cavity surface or bulk material due to thermal breakdown caused by excessively high temperature, and thus avoiding COD phenomenon.
[0016] 2. Using the preparation method of this invention, an AlN nucleation layer is first grown at low temperature on a GaAs substrate to provide adsorption sites for graphite nanosheets. Then, an AlN epitaxial layer is grown at high temperature to provide epitaxial nucleation sites. An aerosol of graphite nanosheet dispersion, along with TMAl, TMGa, AsH3, and H2, is fed into a reaction chamber to grow a graphite nanosheet composite AlGaAs N-confined layer. Because the in-plane thermal conductivity of graphite nanosheets is as high as 2000–5000 W / (m·K), far exceeding that of traditional semiconductor materials such as GaAs (55 W / (m·K), the graphite nanosheets act as lateral thermal channels, rapidly transferring heat from the N-confined layer to the heat sink, reducing the temperature of the active region and minimizing the COD risk caused by heat accumulation.
[0017] 3. The present invention has multiple advantages in directly preparing graphite layers through epitaxial growth technology: 1) It can form atomic-level close contact with semiconductor materials, significantly reducing interfacial thermal resistance; 2) It is more suitable for large-scale production and has better cost-effectiveness; 3) Selective growth can avoid the short-circuit risk caused by the conductivity of graphite, without the need for additional insulating layer processes.
[0018] Embedding a graphite nanosheet heat dissipation layer with a thermal conductivity of 2000–5000 W / (m·K) inside the epitaxial structure of a high-power semiconductor laser can significantly improve the thermal management performance of the device. This heat dissipation layer can quickly conduct heat from the epitaxial layer laterally to the heat sink through its ultra-high in-plane thermal conductivity, effectively reducing the operating temperature of the active region and reducing the cavity surface temperature rise caused by heat accumulation, thereby significantly suppressing the risk of COD. This thermal management strategy is particularly suitable for GaAs-based high-power lasers because GaAs material itself has low thermal conductivity and decreases with increasing temperature. Traditional heat dissipation methods are difficult to meet the heat dissipation requirements under high power density. The high thermal conductivity of graphite nanosheets can make up for this deficiency. Pre-synthesized graphite nanosheets are introduced simultaneously during the growth of the AlGaAsN confinement layer. The distribution density and orientation of the graphite nanosheets are optimized by covering and confining the aggregation of the nanosheets through the epitaxial layer. This innovative heat dissipation solution achieves efficient heat dissipation without compromising the electrical and optical performance of the laser. It also addresses the thermal mismatch between graphite nanosheets and semiconductor materials through interface engineering. For example, ultrathin hBN or AlN can be used as an interface buffer layer to reduce phonon scattering. The flexible structure of ultrathin hBN can alleviate lattice mismatch stress through slight deformation, while the compatibility of AlN's wurtzite structure with III-V semiconductors can further reduce interface scattering. This innovative heat dissipation solution not only improves the laser's heat dissipation capacity and operational reliability but also effectively suppresses COD (Coefficient of Degradation) and extends device lifespan, providing a new technological path for developing higher-power and more stable semiconductor lasers. Attached Figure Description
[0019] The present invention will be further described below with reference to the accompanying drawings and embodiments: Figure 1 This is a schematic diagram of the structure of the laser epitaxial wafer described in this invention. Detailed Implementation
[0020] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments.
[0021] like Figure 1 As shown, a GaAs semiconductor laser epitaxial wafer is epitaxially grown on a GaAs substrate using MOCVD technology. From bottom to top, it includes a GaAs buffer layer, an AlN dielectric layer, an Alx1Ga1-x1As: graphite nanosheet N-confinement layer, an Alx2Ga1-x2As N-waveguide layer, an Alx3Ga1-x3As lower barrier layer, an Inx4Ga1-x4As quantum well layer, an Alx5Ga1-x5As upper barrier layer, an Alx6Ga1-x6As P-waveguide layer, an Alx7Ga1-x7As P-confinement layer, and a GaAs ohmic contact layer. Among them, the GaAs buffer layer is used to alleviate the lattice mismatch and thermal expansion coefficient difference between the substrate and the epitaxial layer, reduce defects, and improve the crystal quality of subsequent epitaxial layers; the AlN dielectric adhesion layer can alleviate the interface stress between the buffer layer and the N-confinement layer; the Alx1Ga1-x1As: graphite nanosheet N-confinement layer restricts electron diffusion to the P side through a high band gap and uses low refractive index characteristics to confine the light field near the active region. Graphite nanosheets have high thermal conductivity, and embedding them in the epitaxial layer can shorten the thermal path and quickly dissipate heat from the active region; the N-waveguide layer and P-waveguide layer have refractive indices between the confinement layer and the active region, constrain the laser mode in the vertical growth direction, and assist electron injection into the active region; the lower barrier layer, quantum well layer, and upper barrier layer together constitute the quantum well structure, confining charge carriers in the quantum well and improving radiative recombination efficiency; the GaAs ohmic contact layer forms a low-resistance ohmic contact with the metal electrode to reduce heat loss.
[0022] This invention improves the heat dissipation efficiency and COD threshold of a GaAs semiconductor laser by introducing graphite nanosheets into the epitaxial structure of the laser.
[0023] A method for fabricating a GaAs semiconductor laser epitaxial wafer includes the following steps: 1) Place the GaAs substrate in the reaction chamber of the MOCVD equipment, and introduce AsH3 in an H2 environment to perform high-temperature heat treatment on the GaAs substrate to remove water and oxygen on the substrate surface, forming an atomically clean GaAs surface, ensuring atomic-level bonding between the epitaxial layer and the substrate, and reducing interface defects. The GaAs substrate is placed in the reaction chamber of the MOCVD equipment, and AsH3 is introduced into the H2 environment to perform high-temperature heat treatment on the GaAs substrate to remove water and oxygen from the substrate surface, forming an atomically clean GaAs surface. This ensures atomic-level bonding between the epitaxial layer and the substrate and reduces interface defects. Since GaAs material tends to decompose at high temperatures, the arsenic in it will volatilize. After introducing AsH3, the arsenic atmosphere generated by the decomposition of AsH3 can maintain a high arsenic partial pressure in the reaction environment, thereby inhibiting the decomposition of GaAs, protecting the structural and compositional stability of the substrate, and avoiding crystal structure damage and compositional changes caused by arsenic volatilization. A further optimized technical solution is that the high-temperature heat treatment temperature is 600–750°C, and the heat treatment time is 10–20 minutes. If the temperature is too low, the oxide removal will be incomplete; if the temperature is too high, it may lead to thermal decomposition of the substrate or surface roughening. Incomplete heat treatment will result in an increase in the interface state density of the epitaxial layer, an increase in nonradiative recombination centers, and a decrease in the internal quantum efficiency (IQE) and lifetime of the laser.
[0024] The high-temperature heat treatment temperature is 740℃, and the heat treatment time is 15 minutes; 2) The reaction chamber temperature is maintained at 710-730℃, and TMGa and AsH3 are introduced to grow a GaAs buffer layer with a thickness of 100-200nm on the GaAs substrate. Preferably, the reaction chamber temperature is 720℃, the growth thickness is 150nm, the doping concentration is 1E18~3E18 atoms / cm³, and the doping source is Si2H6; The preferred doping concentration is 2E18 atoms / cm³.
[0025] 3) When the reaction chamber temperature drops to 650-700℃, NH3 is first introduced for pre-passivation, and then TMAl is introduced to grow an AlN nucleation layer with a thickness of 2-5nm on the GaAs buffer layer; when the reaction chamber temperature rises to 800-900℃, an AlN epitaxial layer with a thickness of 5-10nm is grown on the AlN nucleation layer. 4) When the temperature of the reaction chamber drops to 550-650℃, TMAl, TMGa, AsH3 and graphite nanosheet aerosol are introduced to grow an Alx1Ga1-x1As: graphite nanosheet N confinement layer with a thickness of 1-3μm on the AlN epitaxial layer. Preferably, when the reaction chamber temperature is 600℃, the growth thickness is 2μm, 0.3≤x1≤0.6, the doping concentration is 5E17~2E18 atoms / cm³, and the doping source is Si2H6; Preferably, x1=0.35, and the doping concentration is 1E18 atoms / cm³.
[0026] 5) After step 4) is completed, the temperature of the reaction chamber is raised to 680-700℃, and then TMAl, TMGa and AsH3 are introduced to grow an Alx2Ga1-x2As N waveguide layer with a thickness of 0.5-1.5μm. Preferably, the reaction chamber temperature is 690℃, the growth thickness is 1.0μm, 0.2≤x2≤0.3, the doping concentration is 5E17~2E18 atoms / cm³, and the doping source is Si2H6; Preferably, x2=0.25, and the doping concentration is 5E17 atoms / cm³.
[0027] 6) After step 5) is completed, the temperature of the reaction chamber is reduced to 550-570℃, and then TMGa and AsH3 are introduced to grow the Alx3Ga1-x3As lower barrier layer with a thickness of 20-30nm. Preferably, the reaction chamber temperature is 560℃, the growth thickness is 25nm, and 0.2≤x3≤0.3; Preferably, x3 = 0.25; 7) After step 6) is completed, maintain the reaction chamber temperature at 550-570℃, and then introduce TMI, TMI, and AsH3 to grow an Inx4Ga1-x4As quantum well layer with a thickness of 5-10 nm. Preferably, the reaction chamber temperature is 560℃, and the growth thickness is 7nm; 0.1≤x4≤0.3; Preferably, x4 = 0.2; 8) After step 7) is completed, the temperature of the reaction chamber is reduced to 550-570℃, and then TMGa and AsH3 are introduced to grow the Alx5Ga1-x5As upper barrier layer with a thickness of 20-30nm. Preferably, the reaction chamber temperature is 560℃, the growth thickness is 25nm, and 0.2≤x5≤0.3; Preferably, x5 = 0.25; 9) After step 8) is completed, the temperature of the reaction chamber is raised to 650-690℃, and then TMAl, TMGa and AsH3 are introduced to grow an Alx6Ga1-x6As P waveguide layer with a thickness of 0.2-0.7μm. Preferably, the reaction chamber temperature is 670℃, the growth thickness is 0.5μm, 0.1≤x6≤0.3, the doping concentration is 2E17~9E17 atoms / cm³, and the doping source is CBr4; Preferably, x6=0.2, and the doping concentration is 5E17 atoms / cm³.
[0028] 10) After step 9) is completed, maintain the reaction chamber temperature to 650-690℃, and then introduce TMAl, TMGa and AsH3 to grow an Alx7Ga1-x7As P confinement layer with a thickness of 0.5-1μm; Preferably, the reaction chamber temperature is 670℃, the growth thickness is 0.8μm, 0.6≤x7≤0.9, the doping concentration is 9E17~2E18 atoms / cm³, and the doping source is CBr4; Preferably, x7=0.8, the doping concentration is 1E18 atoms / cm³, and the doping source is CBr4; 11) When the temperature of the reaction chamber drops to 540-560℃, TMGa and AsH3 are introduced to grow a GaAs ohmic contact layer with a thickness of 200-400 nm on the Alx7Ga1-x7As P confinement layer. The reaction chamber temperature was 550℃, the growth thickness was 300nm, the doping concentration was 1E19~4E19 atoms / cm³, and the doping source was CBr4.
[0029] Preferably, the doping concentration is 3E19 atoms / cm³.
[0030] Table 1 compares the COS aging and electrical parameters of conventional structures and the laser epitaxial wafer structure described in this invention under the same process. This invention has a lower threshold current, higher conversion efficiency, and higher output power than conventional devices at the same current. It also has good aging reliability, demonstrating that the graphite nanosheet composite epitaxial structure of this invention can achieve effective heat dissipation of the laser without reducing its functionality.
[0031] Table 1. Comparison of electrical parameters between the comparative examples and the embodiments under the same process.
[0032] In the description of this invention, the terms "upper," "lower," "front," "rear," "left," "right," "top," "bottom," "vertical," and "horizontal," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only to describe the invention and not to require the invention to be constructed or operated in a specific orientation; therefore, they should not be construed as limitations on the invention. The terms "connected" and "linked" in this invention should be interpreted broadly. For example, they can refer to a connection or a detachable connection; they can refer to a direct connection or an indirect connection through intermediate components. Those skilled in the art can understand the specific meaning of the above terms based on the specific circumstances.
[0033] The above description represents preferred embodiments of the present invention. The specific embodiments are provided solely for a better understanding of the invention's concept. Those skilled in the art will recognize that various improvements or equivalent substitutions can be made based on the principles of the present invention, and these improvements or equivalent substitutions are also considered to fall within the scope of protection of the present invention.
Claims
1. A GaAs semiconductor laser epitaxial wafer, epitaxially grown on a GaAs substrate using MOCVD technology, characterized in that, From bottom to top, the structure includes a GaAs buffer layer, an AlN dielectric layer, a graphite nanosheet N-confinement layer, an N-waveguide layer, a lower barrier layer, a quantum well layer, an upper barrier layer, a P-waveguide layer, a P-confinement layer, and a GaAs ohmic contact layer. The GaAs buffer layer is used to alleviate lattice mismatch and thermal expansion coefficient differences between the substrate and the epitaxial layer. The AlN dielectric layer is used to alleviate interfacial stress between the buffer layer and the N-confinement layer. The graphite nanosheet N-confinement layer is an Alx1Ga1-x1As graphite nanosheet N-confinement layer. The graphite nanosheet N-confinement layer restricts electron diffusion to the P-side through a high band gap and confines the light field near the active region using its low refractive index. The refractive indices of the N-waveguide layer and the P-waveguide layer are between those of the confinement layer and the active region, and are used to constrain the laser mode and assist electron injection into the active region in the vertical growth direction. The lower barrier layer, the quantum well layer, and the upper barrier layer together constitute a quantum well structure, confining charge carriers within the quantum well. The GaAs ohmic contact layer forms a low-resistance ohmic contact with the metal electrode.
2. The GaAs semiconductor laser epitaxial wafer according to claim 1, characterized in that, The waveguide layer is an Alx2Ga1-x2AsN waveguide layer, the lower barrier layer is an Alx3Ga1-x3As lower barrier layer, the quantum well layer is an Inx4Ga1-x4As quantum well layer, the upper barrier layer is an Alx5Ga1-x5As upper barrier layer, the P waveguide layer is an Alx6Ga1-x6As P waveguide layer, and the P confinement layer is an Alx7Ga1-x7As P confinement layer.
3. The method for fabricating a GaAs semiconductor laser epitaxial wafer as described in claim 2, characterized in that, Includes the following steps: 1) Place the GaAs substrate in the reaction chamber of the MOCVD equipment, and introduce AsH3 in an H2 environment to perform high-temperature heat treatment on the GaAs substrate to remove water and oxygen on the substrate surface, forming an atomically clean GaAs surface, ensuring atomic-level bonding between the epitaxial layer and the substrate; after introducing AsH3, the arsenic atmosphere generated by the decomposition of AsH3 maintains a high arsenic partial pressure in the reaction environment, inhibiting the decomposition of GaAs, protecting the structural and compositional stability of the substrate, and avoiding crystal structure damage and compositional changes caused by arsenic volatilization. The temperature of the high-temperature heat treatment is 600-750℃, and the heat treatment time is 10-20 minutes. 2) The reaction chamber temperature is maintained at 710-730℃, and TMGa and AsH3 are introduced to grow a GaAs buffer layer with a thickness of 100-200nm on the GaAs substrate. The doping source is Si2H6. 3) When the reaction chamber temperature drops to 650-700℃, NH3 is first introduced for pre-passivation, and then TMAl is introduced to grow an AlN nucleation layer with a thickness of 2-5nm on the GaAs buffer layer; when the reaction chamber temperature rises to 800-900℃, an AlN epitaxial layer with a thickness of 5-10nm is grown on the AlN nucleation layer. 4) When the temperature of the reaction chamber drops to 550-650℃, TMAl, TMGa, AsH3 and graphite nanosheet aerosol are introduced to grow an Alx1Ga1-x1As graphite nanosheet N-confined layer with a thickness of 1-3μm on the AlN epitaxial layer, with Si2H6 as the doping source. 5) After step 4) is completed, the temperature of the reaction chamber is raised to 680-700℃, and then TMAl, TMGa and AsH3 are introduced to grow an Alx2Ga1-x2AsN waveguide layer with a thickness of 0.5-1.5μm and Si2H6 as the doping source. 6) After step 5) is completed, the temperature of the reaction chamber is reduced to 550-570℃, and then TMGa and AsH3 are introduced to grow the Alx3Ga1-x3As lower barrier layer with a thickness of 20-30nm. 7) After step 6) is completed, maintain the reaction chamber temperature at 550-570℃, and then introduce TMI, TMI, and AsH3 to grow an Inx4Ga1-x4As quantum well layer with a thickness of 5-10 nm. 8) After step 7) is completed, the temperature of the reaction chamber is reduced to 550-570℃, and then TMGa and AsH3 are introduced to grow the Alx5Ga1-x5As upper barrier layer with a thickness of 20-30nm. 9) After step 8) is completed, the temperature of the reaction chamber is raised to 650-690℃, and then TMAl, TMGa and AsH3 are introduced to grow an Alx6Ga1-x6As P waveguide layer with a thickness of 0.2-0.7μm and CBr4 as the doping source. 10) After step 9) is completed, maintain the reaction chamber temperature to 650-690℃, and then introduce TMAl, TMGa and AsH3 to grow an Alx7Ga1-x7AsP confinement layer with a thickness of 0.5-1μm and CBr4 as the doping source. 11) When the temperature of the reaction chamber drops to 540-560℃, TMGa and AsH3 are introduced to grow a GaAs ohmic contact layer with a thickness of 200-400nm on the Alx7Ga1-x7AsP confinement layer, with CBr4 as the doping source.
4. The method for fabricating a GaAs semiconductor laser epitaxial wafer as described in claim 3, characterized in that, The temperature of the high-temperature heat treatment in step 1) is 730-750℃.
5. The method for fabricating a GaAs semiconductor laser epitaxial wafer as described in claim 3, characterized in that, The reaction chamber temperature in step 2) is 720℃, the growth thickness is 150nm, and the doping concentration is 1E18~3E18 atoms / cm³. In step 4), when the reaction chamber temperature is 600℃, the growth thickness is 2μm, 0.3≤x1≤0.6, and the doping concentration is 5E17~2E18 atoms / cm³.
6. The method for fabricating a GaAs semiconductor laser epitaxial wafer as described in claim 3, characterized in that, In step 5), the reaction chamber temperature is 690℃, the growth thickness is 1.0μm, 0.2≤x2≤0.3, and the doping concentration is 5E17~2E18 atoms / cm³.
7. The method for fabricating a GaAs semiconductor laser epitaxial wafer as described in claim 3, characterized in that, In step 6), the reaction chamber temperature is 560℃, the growth thickness is 25nm, and 0.2≤x3≤0.3; In step 7), the reaction chamber temperature is 560℃, and the growth thickness is 7nm; 0.1≤x4≤0.3; In step 8), the reaction chamber temperature is 560℃, the growth thickness is 25nm, and 0.2≤x5≤0.
3.
8. The method for fabricating a GaAs semiconductor laser epitaxial wafer as described in claim 3, characterized in that, In step 9), the reaction chamber temperature is 670℃, the growth thickness is 0.5μm, 0.1≤x6≤0.3, and the doping concentration is 2E17~9E17 atoms / cm³.
9. The method for fabricating a GaAs semiconductor laser epitaxial wafer as described in claim 3, characterized in that, In step 10), the reaction chamber temperature is 670℃, the growth thickness is 0.8μm, 0.6≤x7≤0.9, and the doping concentration is 9E17~2E18 atoms / cm³.
10. The method for fabricating a GaAs semiconductor laser epitaxial wafer as described in claim 3, characterized in that, In step 11), the reaction chamber temperature is 550℃, the growth thickness is 300nm, and the doping concentration is 1E19~4E19 atoms / cm³.
Citation Information
Patent Citations
Anti-light-mixing semiconductor laser and preparation method thereof
CN112421377A
VCSEL laser with InGaN electron deceleration layer
CN216929168U